Ukrainian flora checklist. 12: family Boraginaceae (incl. Heliotropiaceae, Hydrophyllaceae) (Boraginales, Angiosperms) (CHORNOMORSKI BOTANICAL JOURNAL, 2024)
Materials and methods: herbarium collections, literature data, field observations. Nomenclature: POWO 2024, World Plants 2024, Euro+Med 2024. Results: In the flora of Ukraine, the family Boraginaceae, including Heliotropiaceae (genera Heliotropium, Argusia) and Hydrophyllaceae (genus Phacelia), includes 32 genera and 100 species (including cultivated ones). Two more species can potentially be found in Ukraine (Myosotis variabilis, Pulmonaria officinalis). The genus Anchusa is represented by 12 species, including two species of the genus Lycopsis (L. arvensis = Anchusa arvensis; L. orientalis = A. ovata). Anchusa popovii, previously cited in the Ukrainian taxonomic literature as a separate species, is a taxonomic synonym of A. ochroleuca. A synonym of Buglossoides rochelii is B. czernjajevii. New to the flora of Ukraine are the genera Cynoglottis, isolated from the genus Anchusa (Cynoglottis barrelieri = Anchusa barrelieri), Iberodes, isolated from the genus Omphalodes (Iberodes linifolia = Omphalodes linifolia, cultivated), Memoremea, also isolated from the genus Omphalodes (Memoremea scorpioides = Omphalodes scorpioides) and Pontechium, isolated from the genus Echium (Pontechium maculatum = Echium maculatum). Argusia sibirica (= Tournefortia sibirica) is considered to be part of the genus Heliotropium (H. sibiricum). Lappula semicincta, previously cited in the Ukrainian taxonomic literature as a separate species, is a taxonomic synonym of L. heteracantha. In Ukraine, 19 species of the genus Myosotis are known to exist. Myosotis laxa is a North American-Norwegian species/subspecies and was erroneously cited for Ukraine (instead of Myosotis cespitosa). Synonyms of Myosotis scorpioides are M. laxiflora and M. strigulosa, which were given as separate species. Myosotis stricta was previously mistakenly cited for Ukraine as Myosotis micrantha, the name of which is synonymous with a completely different species, Arnebia decumbens, which does not grow in Ukraine. In the Carpathians and western regions, it is possible to find Myosotis variabilis (M. decumbens subsp. variabilis), which is erroneously cited as M. decumbens. However, the type species/subspecies grows only in Scandinavia and Western Europe and does not enter Ukraine. Significant nomenclatural changes have occurred in the genus Onosma. In particular, the taxonomic synonym of O. arenaria is O. graniticola. The synonym of O. simplicissima is O. tanaitica. Synonyms for Onosma tinctoria are O. pseudotinctoria and O. subtinctoria. Synonyms for Onosma visianii are O. lipskyi and O. macrochaeta. There are also nomenclatural changes in the genus Symphytum. Synonyms of the typical Symphytum officinale are S. besseri and S. microcalyx. The name S. popovii is synonymous with S. tuberosum subsp. angustifolium. It differs from the typical Western European S. tuberosum subsp. tuberosum by having fewer stem leaves, sepals shorter than the corolla tube, a longer corolla and smaller nuts.
Keywords: annotated list, distribution, species, subspecies, genus, family, systematics, nomenclature, synonyms, herbarium specimens